Studies on some Libyan species of Pamphagidae (Orthoptera: Acridoidea) - Usmani, Mohammad Kamil (Zootaxa, 2007)
The present study is based on eight species representing five genera and two subfamilies belonging to the family Pamphagidae. Specimens from twenty eight localities in Fezzan region (Southern Libya) infesting various cultivated and wild plants were collected. Brief diagnosis of the family Pamphagidae is given. Key to the subfamilies and genera belonging to this family is provided mainly based on conventional as well as genitalic characters. Additional characters of male and female genitalia at generic level and differentiating characters of all species are briefly described. This is the first systematic collection of Pamphagidae from this region. Two species, Tmethis cisti and T. maroccanus were recorded for the first time from Fezzan region.